2019
DOI: 10.1186/s13148-018-0587-8
|View full text |Cite
|
Sign up to set email alerts
|

The role and mechanisms of action of microRNAs in cancer drug resistance

Abstract: MicroRNAs (miRNAs) are small non-coding RNAs with a length of about 19–25 nt, which can regulate various target genes and are thus involved in the regulation of a variety of biological and pathological processes, including the formation and development of cancer. Drug resistance in cancer chemotherapy is one of the main obstacles to curing this malignant disease. Statistical data indicate that over 90% of the mortality of patients with cancer is related to drug resistance. Drug resistance of cancer chemotherap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
379
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 548 publications
(414 citation statements)
references
References 247 publications
(249 reference statements)
2
379
0
9
Order By: Relevance
“…Our initial study presented here ignores noncoding genomic alterations. However, noncoding RNAs such as EGRF-AS1 and activating cis elements such as enhancers have previously been implicated in evasion of drug response (67)(68)(69). The intergenic mutations with high allele frequency are present in our provided datasets and provide opportunity for reanalysis or for querying by those interested in a specific noncoding RNA or enhancer.…”
Section: Resultsmentioning
confidence: 99%
“…Our initial study presented here ignores noncoding genomic alterations. However, noncoding RNAs such as EGRF-AS1 and activating cis elements such as enhancers have previously been implicated in evasion of drug response (67)(68)(69). The intergenic mutations with high allele frequency are present in our provided datasets and provide opportunity for reanalysis or for querying by those interested in a specific noncoding RNA or enhancer.…”
Section: Resultsmentioning
confidence: 99%
“…Drug resistance to chemotherapeutic drugs or targeted medicines is an obstacle encountered in NSCLC treatment [21,22]. Besides mRNAs, lncRNAs and miRNAs have been reported to play an important part in the drug resistance of cancers [23,24,25]. In fact, some lncRNAs and miRNAs have been demonstrated to take part in drug resistance to chemotherapeutic drugs or targeted medicines of NSCLC, including lncRNA TUG1 related to 5-fluorouracil resistance [26], miR-15b related to sunitinib resistance [27].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, mature miRNAs have been reported to impede the expression of targets by targeting them . MicroRNAs occupy a crucial position in various biological processes, including tumor metastasis . Recent studies have shown that many miRNAs, such as microRNA‐612 and miRNA‐621, function as tumor suppressors in NSCLC by regulating target genes .…”
Section: Introductionmentioning
confidence: 99%
“…16 MicroRNAs occupy a crucial position in various biological processes, including tumor metastasis. 17 Recent studies have shown that many miRNAs, such as microRNA-612 and miRNA-621, function as tumor suppressors in NSCLC by regulating target genes. 18,19 A previous study found that circFGFR3 facilitates NSCLC progression via targeting miR-22-3p.…”
Section: Introductionmentioning
confidence: 99%